An islanded microgrid energy system with an innovative frequency controller integrating hydrogen-fuel cell - Yildiz, Suleyman; Gunduz, Hasan; Yildirim, Burak; Ozdemir, Mahmut Temel (Elsevier Sci Ltd, 2022)
Nowadays, energy in microgrids may be produced from numerous renewable sources, yet the effective and sustainable use of these resources depends on energy storage systems. As a result, the growth of microgrids relies heavily on hydrogen energy. For load frequency control studies, we propose an approximation model of a microgrid incorporating photovoltaic (PV), biogas and diesel generators, as well as a fuel cell, electrolyzer, and reformer energy storage unit. When the total quantity of renewable energy produced surpasses the amount of power required, the excess energy is transformed to hydrogen using an electrolyzer. In addition, surplus biogas fuel in the system is converted to hydrogen by the reformer and stored. The fuel cell utilizes the hydrogen stored in a battery to generate electricity as required. The unpredictable and nature-dependent structure of renewable energy resources makes it extremely difficult to establish a balance between demand and supply of energy. The microgrid in this study is designed to use Cascade Double-Input Interval Type 2 Fuzzy Logic Controller (C-DIT2FLC) for load frequency regulation. The Improved Salp Swarm Algorithm (ISSA), a modern optimization algorithm for this proposed model, is used to determine the basic parameters of the PI-PD cascade controller. The CDIT2-FLC changes the controller gains estimated by optimization so that the controller performs the load frequency control effectively. Utilizing actual solar radiation data, a load demand shift, and several renewable resource contributing scenarios, the performance of C-DIT2-FLC is evaluated for load frequency control (LFC). In comparison to previous controllers, the proposed controller has obtained frequency response gains varying between 59% and 84% based on the ITAE-performance index (Integral of Time-weighted Absolute Error). According to the research findings, the proposed controller (C-DIT2-FLC) outperforms other controllers in terms of performance.
Keywords: Autonomous Microgrid; Renewable energy; Aqua electrolyzer; Fuel cell; Improved-salp swarm algorithm; Type-2 fuzzy logic